Sustainable Carbene Transfer Reactions with Iron and Light - Empel, Claire; Koenigs, Rene M. (Synlett, 2019)
Carbenes are versatile, highly reactive intermediates with great importance in chemistry. We recently reported on our findings on safe and scalable applications of hazardous diazoacetonitrile using cheap and commercially available iron catalysts in efficient carbene transfer reactions, ranging from cyclopropanation towards C–H functionalization reactions for the synthesis of biologically important building blocks. More lately, we uncovered the reactivity of diazoalkanes under photochemical conditions using visible light and were able to demonstrate a variety of different, metal-free carbene transfer reactions, which now open up new sustainable ways for the construction of small functional molecules.1 Introduction2 Iron-Catalyzed Carbene Transfer Reactions of Diazoacetonitrile3 Metal-free Carbene Transfer Reaction with Visible Light4 Summary
Keywords: carbene transfer reactions; cycloaddition; rearrangement; C–H functionalization; diazoalkanes; iron; photochemistry